Historical and Methodological Analysis of Tafsir Marah Labib by Shaykh Muhammad Nawawi al-Bantani - Syaffira Nur Rajiba; Muhammad Abdul Jalil; Syifa Anjani (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article conducts a comprehensive study of Tafsir Marah Labid (or Tafsir Munir) compiled by Sheikh Nawawi al-Bantani, a prominent scholar in the Indonesian archipelago in the 19th century. This research aims to fill the gap in comprehensive studies of this tafsir by examining the author's biography, the structure of the book, the characteristics of the tafsir, and the methods of interpretation used. Tafsir Marah Labid was compiled in response to a collective request from scholars and was written in Mecca in 1884 AD. It is widely known both in Indonesia and the Middle East, and to this day remains an important reference source in Islamic boarding schools in the archipelago. The main characteristics of this interpretation include concise and compact delivery, using the ijmali (global) method with an emphasis on integrating the views of classical interpreters without excessive personal speculation, in accordance with Nawawi's caution in avoiding tafsir bi ar-ra'yi. A moderate Sufi approach and Shafi'i fiqh are dominant in this tafsir, with references to classical tafsir books and a strong traditional orientation. This study shows that Marah Labid's Tafsir not only represents the continuity of classical Islamic exegesis, but also adapts to the intellectual and religious context in the archipelago, making it a strategic intellectual heritage in the Indonesian Islamic tradition. This research uses qualitative and descriptive analytical library methods with triangulation of primary and secondary sources, presenting the results in an in-depth narrative and revealing the historical and intellectual implications of the work.